2021
DOI: 10.1111/ijmr.12285
|View full text |Cite
|
Sign up to set email alerts
|

A meme‐based research programme for management and organization studies

Abstract: Memes are proposed as cultural equivalents to genes, and meme-based research (memetics) has been undertaken to examine cultural aspects of management and organization studies (MOS). However, variable operationalization of the meme concept for a fragmented range of research topics has hampered the development of a coherent memetic MOS discipline. In particular, there is a largely unrecognized dilemma regarding the ontological status of the meme because it is unclear if the concept represents a real cultural gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Schlaile and Ehrenberger (2016) demonstrate the potential of a similar memetic approach to the study of social entrepreneurship. Memetics has not gained much traction in management studies (Gill and Price, 2022). Perhaps focusing on particular rather than universal memes could help.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schlaile and Ehrenberger (2016) demonstrate the potential of a similar memetic approach to the study of social entrepreneurship. Memetics has not gained much traction in management studies (Gill and Price, 2022). Perhaps focusing on particular rather than universal memes could help.…”
Section: Discussionmentioning
confidence: 99%
“…Paralleling Breslin and Jones (2012), who suggested that entrepreneurial learning could be re-conceptualized as an evolutionary process, this paper conceptualizes pre-organization as a process of cultural evolution and, more specifically, a memetic process. But as Gill and Price (2022) observed, application of memetics to management and organization studies remains nascent. Application to the context of pre-organization is almost non-existent, an exception being Schlaile and Ehrenberger’s (2016) application of memetics to social entrepreneurship, which pioneered the articulation of a meme-based unit of selection in a pre-organization context.…”
Section: A “Gene” For Pre-organizationmentioning
confidence: 99%